Meteorological and hydrological variables on occurrence of riverbank erosion along lower São Francisco river Variáveis meteorológicas e hidrológicas sobre ocorrência de erosão no laixo São Francisco - Igor P. da Rocha; Francisco S. R. Holanda; Renisson N. Araújo Filho; Ana P. B. Casado; Arilmara A. Bandeira (Revista Brasileira de Engenharia Agrícola e Ambiental)
The objectives of this paper were to analyze the seasonal distributions of climatic and hydrological variables along the Lower São Francisco River, Northeastern Brazil, between the States of Sergipe and Alagoas, and further, to verify their relationships with the erosion of the right margin in Sergipe State. The investigated area comprises the sedimentary portions of the Lower São Francisco River, located at the Cotinguiba-Pindoba Irrigated Perimeter. Historical records of variables such as rainfall, river streamflow velocity, river discharge, wind velocity and the predominant direction were collected from a climatological station as well as rain and streamflow gauges located in the municipality of Propriá. The rainfall that occurs in the region is considered non-erosive, 96.2% of the rain had intensity less than 25.0 mm h-1. The evolution of erosion is explained by the increase in the outflow in February that peaked at 9,894.50 m³ s-1 and led to increases in the flow velocity. The rainfall regime interacts with the wind that blows predominantly from the eastern direction during the dry season and from the southeastern direction during the rainy season with maximum velocities of 5.5 and 8.0 m s-1, respectively. O objetivo deste trabalho foi analisar a distribuição sazonal de variáveis climáticas e hidrológicas ao longo do baixo curso do rio São Francisco, nordeste do Brasil, entre os estados de Sergipe e Alagoas e ainda verificar, também, suas relações com a erosão da margem direita no Estado de Sergipe. A área investigada compreende as porções sedimentares do Baixo São Francisco localizada no Perímetro Irrigado Cotinguiba-Pindoba. Foram coletados os registros históricos de variáveis como a precipitação, a velocidade do fluxo do rio, vazão do rio, velocidade do vento e da direção predominante de uma estação climatológica, bem como chuva e medidores de vazão localizados no Município de Propriá. A precipitação que ocorre na região é considerada não-erosiva, 96,2% das chuvas tiveram intensidade menor que 25,0 mm h-1. A evolução da erosão é explicada pelo aumento do fluxo em fevereiro que atingiu um máximo de 9894.50 m³ s-1 e levou a um aumento na velocidade do fluxo. O regime de chuvas interage com o vento, que sopra predominantemente na direção do leste durante a estação seca e da direção sudeste durante a estação chuvosa, com velocidades máximas de 5.5 e 8.0 m s-1, respectivamente.